TIMI SCORE AND MAJOR ADVERSE CARDIOVASCULAR EVENTS IN NSTE-ACS PATIENTS - Hariadi, Rudi; Subandi, Andi; Nasution, Riska Amalya; Nurhusna; Oktaria, Yosi (Jurnal Multidisipliner Kapalamada, 2026)
Non-ST Elevation Acute Coronary Syndrome (NSTE-ACS) is a serious cardiovascular condition associated with a high risk of Major Adverse Cardiovascular Events (MACE), including death, recurrent myocardial infarction, heart failure, arrhythmia, and the need for revascularization. Therefore, accurate risk stratification is crucial for optimal clinical management. This study employed a retrospective analytical observational design to examine the relationship between the Thrombolysis in Myocardial Infarction (TIMI) score and the occurrence of MACE in 69 patients selected purposively from hospital medical records. TIMI scores were categorized as low, intermediate, or high, while MACE events were identified based on clinical records. The results showed that most patients were male (59.4%) aged 45–64 years (53.6%), with the majority having intermediate TIMI scores (68.1%). MACE events occurred more frequently in patients with intermediate and high TIMI scores. Gamma correlation analysis indicated a strong and significant association between TIMI scores and MACE (r = 0.881; p < 0.001). These findings suggest that the TIMI score is an effective tool for clinical risk stratification in NSTE-ACS patients.